Muscarinic Modulation of High Frequency Oscillations in Pedunculopontine Neurons - Kezunovic, Nebojsa; Hyde, James R.; Goitia, Belen; Bisagno, Veronica; Urbano, Francisco J.; Garcia-Rill, Edgar (Frontiers in Neurology, 2013)
We previously reported that persistent application of the nonspecific cholinergic agonist carbachol (CAR) increased the frequency of calcium channel-mediated oscillatory activity in PPN neurons, which we identified as dependent on voltage-gated, high threshold P/Q-type channels. Here, we tested the hypothesis that M2 muscarinic receptors and G-proteins associated with M2 receptors mediate the increase in oscillatory frequency in PPN neurons. We found, using depolarizing ramps, that patch clamped 9-12 day old rat PPN neurons (n=189) reached their peak oscillatory activity around -20 mV membrane potential. Acute (short duration) application of CAR blocked the oscillatory activity through M2 muscarinic receptors, an effect blocked by atropine. However, persistent (long duration) application of CAR significantly increased the frequency of oscillatory activity in PPN neurons through M2 receptors [40±1 Hz (with CAR) vs 23±1 Hz (without CAR); p